Four-dimensional flow magnetic resonance imaging analysis before and after thoracic endovascular aortic repair of chronic type B aortic dissection. (17th September 2018) - Takei, Yusuke; Itatani, Keiichi; Miyazaki, Shohei; Shibasaki, Ikuko; Fukuda, Hirotsugu
Abstract: OBJECTIVES: The purpose of this study was to calculate the changes in the blood flow direction and volume in the aortic lumen and at the entry and re-entry sites using 4-dimensional (4D) phase-contrast magnetic resonance imaging (MRI) after performing entry closure with thoracic endovascular aortic repair for chronic DeBakey IIIb aortic dissection. METHODS: Aortic blood flow was analysed at 3 phases with 4D phase-contrast MRI in a single therapeutic DeBakey IIIb aortic dissection case. RESULTS: Primary entry was in the distal arch, and there were 4 re-entry sites downstream in the diaphragm. Preoperatively, the entry site formed a large antegrade flow (1082 ml/min) to the 4 re-entry sites, but soon after the closure of the entry site, re-entry sites 1 through 3 became a new entry site whose flow pattern changed retrogradely, resulting in increased volume in the false lumen in the acute phase, whereas the flow at the previous re-entry sites from the true lumen to the false lumen decreased gradually, resulting in aortic remodelling with a reduction in the size of the false lumen: the preoperative, postoperative and 6-month postoperative mean flow volumes (ml/min) were 23, 254 and 173 at re-entry site 1; 59, 887 and 279 at re-entry site 2; and 303, 608 and 103 at re-entry site 3. The changes in the flow volume of the false lumen followed a similar trend expect for the area around the abdominal aorta. CONCLUSIONS: The volume of flow at the entry site was high, and closure of the primary entry site during thoracic endovascular aortic repair is very important. These changes in the flow volume of the re-entry sites and the false lumen may affect volume changes in the false lumen.